Identidades e diferenças: o caso da guerra civil na antiga Iugoslávia - Mathias, Ana Luiza Terra Costa [UNESP]; Aguilar, Sérgio Luiz Cruz [UNESP] (My University, 2012)
Abstract: The civil war in the former Yugoslavia (1991 - 1995) had a strong ethnicreligious component. In an attempt to maintain the cohesion of an artificially created state post-first World War, identities were sought and accepted - and institutionalized - the differences between the various peoples that constituted the "land of the South Slavs". From the 1980s the differences were highlighted during the war and taken to the extreme, especially in the territories of Croatia and BosniaHerzegovina. From literature and the author's personal experience and using concepts of culture, ethnicity, identity, difference, belonging, nation and state, the text shows how the ethnic-religious differences were used during the civil war in Yugoslavia to claim possession of territories, strengthen discourse of the impossibility of coexistence, overvalue potential threats and fear and justify the perpetration of crimes against humanity.

A guerra civil na antiga Iugoslávia (1991 – 1995) teveum forte componente étnico – religioso. Na tentativa de manter a coesão de um Estado criado artificialmente pós-1ª Guerra Mundial, foram buscadas identidades e aceitas - e institucionalizadas - as diferenças entre os diversos povos que constituíam a “terra dos eslavos do sul”. A partir da década de 1980 as diferenças foram realçadas e durante a guerra levadas ao extremo, especialmente nos territórios da Croácia e da Bósnia Herzegovina. A partir de pesquisa bibliográfica e da experiência pessoal do autor e, utilizando conceitos de cultura, etnia, identidades, diferenças, pertencimento, nação e Estado, o texto apresenta como as diferenças étnico-religiosas foram utilizadas durante a guerra civil na Iugoslávia para reivindicar a posse de territórios, fortalecer o discurso da impossibilidade de convivência, supervalorizar possíveis ameaças e medo e justificar o cometimento de crimes contra a humanidade.
Keywords: Iugoslávia; Etnia; Guerra civil